2021
DOI: 10.2147/ijn.s334965
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Nanoparticles Inhibiting Ferroptosis for the Enhanced Treatment of Intracerebral Hemorrhage

Abstract: Background Intracerebral hemorrhage (ICH) is a form of severe stroke, the pathology of which is tied closely to a recently discovered form of programmed cell death known as ferroptosis. Curcumin (Cur) is a common phenolic compound extracted from the rhizome of Curcuma longa capable of hematoma volume and associated neurological damage in the context of ICH. Despite exhibiting therapeutic promise, the efficacy of Cur is challenged by its poor water solubility, limited ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 48 publications
(55 reference statements)
1
28
0
Order By: Relevance
“…Intracerebral hemorrhage (ICH) is a type of severe stroke, the pathology of which is closely related to ferroptosis. Curcumin nanoparticles inhibit ferroptosis and enhance ICH treatment [129], and baicalin can also suppress ferroptosis in ICH [130]. Tau-mediated iron export inhibits ferroptosis after ischemic stroke [131].…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Intracerebral hemorrhage (ICH) is a type of severe stroke, the pathology of which is closely related to ferroptosis. Curcumin nanoparticles inhibit ferroptosis and enhance ICH treatment [129], and baicalin can also suppress ferroptosis in ICH [130]. Tau-mediated iron export inhibits ferroptosis after ischemic stroke [131].…”
Section: Strokementioning
confidence: 99%
“…Curcumin decreases rhabdomyolysis-related renal damage by reducing ferroptosis, and mechanistic studies have shown that curcumin downregulates the TLR4/NF-κB axis and activates HO-1 [220]. Since curcumin nanoparticles suppress ferroptosis, they can be used to strengthen the treatment of ICH [129]. Curcumin also induces the ferroptosis of breast cancer cells by upregulating SLC1A5 [99].…”
Section: Regulatory Effects Of Food-borne Active Ingredients On Ferro...mentioning
confidence: 99%
“…Chen et al, demonstrated that a curcumin analog could induce ferroptosis and suppress GPX4 [ 141 ]. Another study by Yan et al, utilized curcumin nanoparticles and demonstrated an opposing effect of ferroptosis inhibition [ 142 ]. Information on the connection between curcumin and its effects on ferroptosis in endometriosis is still limited and needs further investigation.…”
Section: Treatments For Oxidative Stressmentioning
confidence: 99%
“…Clinical trials have suggested that 3.6 g of curcumin taken orally for cancer treatment is a therapeutically effective dosage [ 146 ]. Various formulations of curcumin have been produced to address the issues of its pharmacokinetics, poor bioavailability, and low solubility when taken orally [ 142 , 147 ]. Some of these formulations include phospholipid complexes, micelles, liposomes, nanoparticles, and micro-formulations which increase the solubility and improve its cellular uptake [ 147 ].…”
Section: Treatments For Oxidative Stressmentioning
confidence: 99%
“… 128 One of the most promising approaches involving the use of curcumin is represented by the exploitation of nanostructures composed mostly of curcumin, commonly referred to as “nanocurcumin”. 126 , 131 134 Nanocurcumin is commonly obtained through precipitation methods, usually in the presence of stabilizers such as polyethylene glycol (PEG) 126 or polyvinylpyrrolidone (PVP). 131 Nanocurcumin has shown potential for the treatment of neurological diseases not only in animals (such as on in vivo models of MS 132 ) but also even in clinical trials.…”
Section: Antioxidant Extract-loaded Nanocarriersmentioning
confidence: 99%